Optimasi Pengembangan Lahan Berbasis Daerah Irigasi di Provinsi Sulawesi Selatan - Widya Utaminingsih; Edy Anto Soentoro; Winskayati Winskayati; Eko Winar Irianto (Balai Teknik Irigasi, 2017)
Food security has been transformed into one of the strategic issue when it is related to the raise of population numbers and the high rate of irrigated land conversion into residential/industry. The increase of rice national production becomes one of the Government’s key element to meet the national food necessity. The zonation mapping process to the irrigated area potency has been conducted, however, the further analysis to determine the land development policy is necessary in correspond with the raise of production cost and investment expense. This is essential to assess its development efficacy. The main purpose of this research is to examine the best scheme to boost up the national rice productivity, either through the extentification or the intentification processes and to calculate the minimum required of the investment cost. This research is focused on the analysis towards the irrigated area, whereas the location determination is referring to these two important aspects: 1) the zonation mapping potency of irrigated land development; and 2) the simulation of categorization of the national rice productivity. The optimization process has been investigated through Multi Criteria Decision Analysis (MCDA) along with the Analytical Hierarchy Process (AHP) method. Further more in-depth scoring criteria has been canducted with the compromise Programming and Promethee methods to figure out the development priority. The total Investment cost which acquired for the average irrigated area extensification was estimated around 105,6 million IDR/ha, henceforth, it is could be referred as the basis for budgeting- stipulation process for the future irrigated area development, with the production increase resulted from the abovementioned extensification of irrigated area was 5,02 tonnes/ha, or the cost of investment per production for the pertinent irrigated area intensification was 10,51 million IDR/ton.